2017
DOI: 10.1136/bcr-2017-219624
|View full text |Cite
|
Sign up to set email alerts
|

Huge cardiac myxoma in pregnancy

Abstract: A 28-year-old pregnant woman presented at 28 weeks of gestation. She was diagnosed to have a left atrial myxoma 2 years earlier, but was lost to follow-up. During this pregnancy, the transthoracic echocardiography showed a 9 cm mass in the left atrium obstructing mitral valve inflow, interfering with mitral valve closure, causing severe mitral regurgitation and severe pulmonary hypertension. However, there were no clinical signs of pulmonary and systemic congestion or obstruction. Based on the clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…The decision to postpone it to after delivery depends on the gestational age of pregnancy, worsening symptoms, and the echocardiography findings. Traisrisilp et al, 20 reported a large (9 cm) cardiac myxoma in the left atrium diagnosed at 28 weeks gestation. Being asymptomatic, the patient was allowed to continue her pregnancy to full term.…”
Section: Discussionmentioning
confidence: 99%
“…The decision to postpone it to after delivery depends on the gestational age of pregnancy, worsening symptoms, and the echocardiography findings. Traisrisilp et al, 20 reported a large (9 cm) cardiac myxoma in the left atrium diagnosed at 28 weeks gestation. Being asymptomatic, the patient was allowed to continue her pregnancy to full term.…”
Section: Discussionmentioning
confidence: 99%
“…If the tumor is diagnosed after the rst trimester but before the late third trimester, surgery is supposed to be carried out without delay. If the diagnosis takes place in the third trimester of pregnancy, delivery via cesarean section should be carried out rst, in view of the consensus that fetus in this trimester would gain a high probability of survival without severe complications [15]. Our management strategies were the same as those of Traisrisilp.…”
Section: Discussion Andmentioning
confidence: 99%
“…Myxoma during pregnancy is extremely rare; some individual cases are described in the literature [2], [4]. Pregnant women are a vulnerable group.…”
Section: Discussionmentioning
confidence: 99%